General Semantics: A Science for Common Life - Trujillo Liñán, Laura (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The language, concepts, and scientific theories from which the world and society have been built have been developed from the influence of intellectuals who dedicated their lives to building science from scratch like the ancient Greeks and more in specifically Aristotle. However, science is not attached to everyday situations, daily life, hence the theory of General Semantics by Alfred Korzybski that proposes a new non-Aristotelian theory more in line with people, with everyday life.